PARTISIPASI MAHASISWA KKN DALAM KEGIATAN SOSIALISASI DAN PENYULUHAN HUKUM PENDAFTARAN TANAH SISTEM LENGKAP DI DESA JATI PASAR MOJOKERTO - Yulianingsih, Wiwin; Hutagalung, Iqbal; Abiba, Anggela Maulita; Betty Storus, Marlin Noviardana; Prisma (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The program created by the government is one of them to organize a Complete Land Registration System (PTSL) mechanism. This program has been implemented since 2018. The purpose of this program is to facilitate, expedite, and accelerate the provision of legal protection for land rights and provide legal certainty for those who own the land and the Indonesian people so that their administration is orderly in land. The author conducted this study with the aim of analyzing the obstacles in the Jati Pasar community, Mojokerto Regency in dealing with the PTSL government program and how much the Jati Pasar community, Mojokerto Regency understands the program. This research method uses an empirical method by directly conducting sales with the community as well as the Head of Jati Pasar Village, Mojokerto Regency. The results of this study indicate that there are still many people in Jati Pasar Village, Mojokerto Regency who do not understand the government's complete land registration system (PTSL) program and many people still experience obstacles while running this program.